In Vitro Drug Screening of Cell Culture Models for LMNA-Related Dilated Cardiomyopathy - Turunen, Minttu (My University, 2023)
Mutations in the LMNA gene encoding lamins A and C cause inherited diseases commonly called laminopathies. The most common laminopathy is dilated cardiomyopathy (DCM) and currently, there are no specific treatments for the disease. This study aimed to identify drugs that affect cell viability and morphology of lamin mutant cells. Dermal fibroblasts from a DCM patient carrying the p.S143P-LMNA mutation and from a healthy donor were screened with 166 drugs using imaging-based analysis. Based on cell viability, the most interesting drugs were selected for further testing on neonatal cardiomyocytes isolated from transgenic p.S143P-Lmna mice and on human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) from DCM-patient and healthy control. The effects of the selected drugs (glimepiride, nicorandil, sotagliflozin, 4-PBA and gemcitabine) on cell viability and lamin A and C protein expression were further investigated after 72-hour incubations. Additionally, immunofluorescence stainings were used to visualize the lamina structure (lamin A/C), actin cytoskeleton (F-actin), cardiomyocyte sarcomere structure (a-actinin) and DNA damage (γH2AX). Similar results in cell viability could not be reproduced using an ATP-based assay and viability between isolated neonatal cardiomyocytes from LmnaWT/WT and LmnaS143P/S143P mice remained unaffected. Also, no obvious damage in the lamina, sarcomere structure or actin cytoskeleton was detected. Major defects in heterochromatin organization were found in the LmnaS143P/S143P mouse cardiomyocytes, however, the chosen drugs were unable to restore such changes. Since previous reports have shown that DCM-linked cellular defects manifest particularly under external stress, it would be important to investigate the impact of drugs under stressed conditions in the future.
Keywords: LMNA, laminopathy, dilated cardiomyopathy, drug screening